Hodja Ahmet Yasawi And The Basıs of His Education System - ERGESHOV, Ermamat; YEGENOV, Nurali (Scientific Journal of Faculty of Theology, 2018)
Mankind today in many areas, as in the past period, faced with the problem that led to the crisis itself. As seen with solutions can not be easily overcome, but can provide an environment which can restore human comfort. The most important thing is to realize that it - not a story repeated and mistakes can. In this follow in the footsteps of outstanding scientists of the Turkish Muslim peoples and recognized by more opinions make up their systematic philosophical instruction as well as their experiences in dealing with vital issues - is considered for each person as an individual and social obligations. That is why the stands prominently - methods successors of the Prophet, which they followed to resolve any problems at the time. It's just perfect for mankind and has the advantage for the benefit of mankind. Thus it is possible to revive the "ideal" for humanity as a whole and in particular for Muslims. As well as this will help to strengthen the moral principles and the expansion philosophical foundations of life. In this context, the article was written considering for major work Divan-i Hikmet by Hodja Ahmet Yasawi. Alsol provided information on the philosophical basis of all the methods that he used, the approach of "language" and "religion", his efforts to explain and teach Islam and as well as his educational philosophy methods for expansion of Islam especially to the lives of Turkish nations.